Burden and cost of communicable, maternal, perinatal and nutrition deficiency diseases in India. (24th September 2020) - Yadav, Jeetendra; Menon, Geetha R; Mitra, Malvika; Allarakha, Shaziya; John, Denny
Abstract: Background: Globally 36% of deaths and 42% of Disability Adjusted Life Years (DALYs) are due to communicable, maternal, perinatal and nutritional disorders (CMPND). We examined the state-wise disease burden and treatment cost for these diseases in India for 2017. Methods: DALYs for CMPND was obtained from National Disease Burden Estimate (NBE) Study and the expenditure was determined from the unit level records of persons who reported hospitalization for one or more CMPND in National Sample Survey (NSS)—75th Round. Results: The top conditions resulting in high DALYs for India were perinatal conditions and nutritional deficiency disorders. Odisha had the highest DALY rate, while Kerala had the lowest DALY rate for CMPNDs. The out-of-pocket expenditure (OOPE) was highest in Chattisgarh, while percentage of households pushed to CHE was highest in Uttar Pradesh for CMPND. Conclusion: The public healthcare facilities need to be strengthened to facilitate patients with CMPND to undergo treatment that is timely, affordable and cost-effective. Efforts should be made for optimization of strategies aimed at primary and secondary prevention of CMPND and reduce OOPE for treatment of these diseases. In addition, advocacy spreading awareness will reduce the burden and treatment expenditure for CMPNDs in India.